El historiador frente al “documento viviente”: La crisis del testimonio y la narración del Holocausto - Pérez Baquero, Rafael (Bollettino Filosofico, 2016)
Our essay deals with the problem regarding the implications that the testimony – as a historiographical source – has for the assumptions of traditional historiography. The theories regarding testimony in the post-war context developed by Dori Laub, Shoshana Felman or Giorgio Agamben, allow us to define testimony as a performative act which affects, on the one hand, the victims who try to reconstruct its torn subjectivity, and, on the other hand, the historian, who is filled with the emotional content derived from this figure. Such condition makes an epistemic requirement impossible: the distance subject-object in the account of the events. Consequently, only the middle voice of the modernist antinarrative allows us to give an account of these events. This methodological imperative disqualifies the autonomy of the historiography from the collective memory.